2022
DOI: 10.1159/000524867
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Traumatic Spinal Cord Injury in Developing Countries from 2009 to 2020: A Systematic Review and Meta-Analysis

Abstract: Introduction: Traumatic spinal cord injury (TSCI) is a catastrophic event with a considerable health and economic burden on individuals and countries. This study was performed to update an earlier systematic review and meta-analysis on epidemiological properties of TSCI in developing countries published in 2013. Methods: Various search methods including online searching in database of EMBASE and PubMed, and hand searching were performed (2012 to May 2020). The keywords ‘Spinal cord injury’, ‘epidemiology’, ‘in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 66 publications
7
25
1
2
Order By: Relevance
“…The complication rate of TSCI in China was estimated at 35%, and the major secondary complications were respiratory and urinary diseases. However, after comparing the results with the developing countries ( 80 ), the results showed that pressure ulcers and urinary tract infections were the most common. In the subgroup analysis, the in-hospital mortality and complication rates in the south were higher than those in the north.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate of TSCI in China was estimated at 35%, and the major secondary complications were respiratory and urinary diseases. However, after comparing the results with the developing countries ( 80 ), the results showed that pressure ulcers and urinary tract infections were the most common. In the subgroup analysis, the in-hospital mortality and complication rates in the south were higher than those in the north.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, falls and car accidents are the main causes [2]. Recently, the trend globally for SCI is for it to affect younger people, mostly under 30 years of age [3]. The occurrence of irreversible motor and sensory impairment following SCI has implications for the whole person [4].…”
Section: Introductionmentioning
confidence: 99%
“…A lesão traumática da medula espinhal (LTME) é a mais prevalente entre as pessoas (GOLESTANI et al, 2022;PEREIRA;DE CASTRO;BARBOSA, 2022). Nesse sentido, estima-se que nos países em desenvolvimento a incidência de LTME é de aproximadamente 22,55 milhões por ano, sendo que 80,09% dos casos ocorrem em pessoas do sexo masculino com idade inferior a 30 anos (GOLESTANI et al, 2022). O nível da LTME mais prevalente é a lesão cervical e a causa mais comum das lesões são os acidentes automobilísticos (GOLESTANI et al, 2022;PEREIRA et al, 2022).…”
Section: Introductionunclassified
“…Nesse sentido, estima-se que nos países em desenvolvimento a incidência de LTME é de aproximadamente 22,55 milhões por ano, sendo que 80,09% dos casos ocorrem em pessoas do sexo masculino com idade inferior a 30 anos (GOLESTANI et al, 2022). O nível da LTME mais prevalente é a lesão cervical e a causa mais comum das lesões são os acidentes automobilísticos (GOLESTANI et al, 2022;PEREIRA et al, 2022).…”
Section: Introductionunclassified